Le Système D’information Comptable Des PME Marocaines : Observation Des Pratiques - Younes El Bakirdi; Said Radi (European Scientific Journal, ESJ, 2017)
By mobilizing the theoretical framework of the specificity of SMEs, this work tries, through the observation of accounting practices, to answer the question of the relevance (production and use) of the accounting data for the managers of Moroccan SMEs. Indeed, through semi-structured individual interviews with SME managers, accounting and financial directors of SMEs and accountants, it is about to describe the different accounting practices of SMEs on the one hand, and to highlight potential determinants that may explain the differentiation of these practices on the other hand.